Rangeland management practices modulated trait-based plant community assembly through environmental filtering in Hulun Buir Steppe - Danyu Wang; Le Wang; Xiaohui Yang; Yuanjun Zhu; SeMyung Kwon; Zhongjie Shi; Jiankang Liu; Tuvshintogtokh Indree (Ecological Indicators)
Eurasian temperate steppes have undergone significant land-use changes in recent decades, leading to a considerable decline in species diversity and community productivity, with implications for sustainable rangeland management. These changes are intricately linked to community assembly processes, with environmental filtering playing a crucial role. However, there is a scarcity of insights into how different management practices influence environmental filtering. To address this knowledge gap and contribute to sustainable rangeland management, we employed the Joint Species Distribution Model (JSDM) to evaluate the impact of three distinct management practices—grazing-only, mowing-only, and grazing-mowing—on environmental filtering and the modulated role of plant functional traits in the Hulun Buir Steppe. Our findings show that for the first time that the type of management significantly influences environmental filtering by altering the soil environment, particularly soil bulk density. The grazing-mowing management type, which introduces the most significant disturbance, was found to enhance the intensity of environmental filtering. Further analysis indicated that community structure under grazing-only management responded more stably to environmental changes, potentially due to the modulating influence of plant productivity and photosynthetic functional traits, such as Leaf Dry Matter Content (LDMC) and Leaf Area Index (LAI). Additionally, the mowing-only management type can sustain high species richness across varying environmental conditions. This study highlights the importance of considering local environmental conditions when selecting rangeland management practices. Integrating plant functional traits into management strategies can help maintain ecological resilience and promote sustainable grassland ecosystems.